Genius - Pons, Alain (Sententiae, 2012)
First Ukrainian translation of Alain Pons’ article "Genius" (Vocabulaire Européen des philosophies. Dictionnaire des intraduisibles. Paris: Seuil, & Le Robert, 2004, pp. 497-502).